Trend and causes of maternal death, stillbirth and neonatal death over seven decades in Hong Kong - Ka Wang Cheung; Mimi Tin Yan Seto; Weilan Wang; Chi Tao Ng; William Wing Kee To; Ernest Hung Yu Ng (Elsevier, 2022)
Summary: Background: Reducing maternal and perinatal mortality is a global objective. Hong Kong is a city with low maternal and perinatal mortality but little is known about the trend and causes of these deaths in this high-income city. We analyzed the maternal death, stillbirth and neonatal death since 1946 in Hong Kong. Methods: Data were extracted from vital statistics, based on the number of registered deaths and births, provided by the Department of Health, the Government of the HKSAR. The annual change rate of mortality was evaluated by regression analysis. Contextual factors were collected to assess the association with mortality. Findings: Between 1946 and 2017, the stillbirth rate (per 1,000 total births) reduced from 21·5 to 2·4; early and late neonatal deaths (per 1,000 live births) reduced from 14·1 and 18·1 to 0·7 and 0·4 in 2017, respectively. The maternal mortality ratio (per 100,000 live births) declined from 125 to 1·8.The causes of maternal and perinatal deaths were available since 1981 and 1980 respectively. The leading causes of death were thromboembolism (37·0%) and obstetric haemorrhage (30·4%) for maternal death; congenital problem (30·1%) and prematurity (29·0%) for neonatal death. No data on causes of stillbirth were available. No specific shift of pattern was observed in the causes of maternal and neonatal death with time. There were no cases of maternal death due to sepsis and only 2 cases (2·2%) of maternal deaths due to indirect cause. Interpretation: The maternal and perinatal death have reduced significantly in Hong Kong and maintained at the lowest level globally. Indirect maternal death and sepsis were unusual causes of maternal deaths. Use of ICD-PM stillbirth classification, setting up a maternal death confidential enquiry and adding pregnancy checkbox could be the next step to identify and categorize hidden burden. Funding: Nil.